Cardiovascular disease after liver transplantation: When, What, and Who Is at Risk. Issue 7 (July 2015) - Fussner, Lynn A.; Heimbach, Julie K.; Fan, Chun; Dierkhising, Ross; Coss, Elizabeth; Leise, Michael D.; Watt, Kymberly D.
<x xml:space="preserve">Abstract</x> The evolution of metabolic and cardiovascular disease (CVD) complications after liver transplantation (LT) is poorly characterized. We aim to illustrate the prevalence of obesity and metabolic syndrome (MS), define the cumulative incidence of CVD, and characterize risk factors associated with these comorbidities after LT. A retrospective review of 455 consecutive LT recipients from 1999 to 2004 with an 8‐ to 12‐year follow‐up was performed. Obesity increased from 23.8% (4 months) to 40.8% (3 years) after LT. Increase in body mass index predicted MS at 1 year after LT (odds ratio, 1.1; P < 0.001, per point). CVD developed in 10.6%, 20.7%, and 30.3% of recipients within 1, 5, and 8 years, respectively. Age, diabetes, hypertension, glomerular filtration rate < 60 mL/minute, prior CVD, ejection fraction < 60%, left ventricular hypertrophy, and serum troponin (TN) > 0.07 ng/mL were associated with CVD on univariate analysis. Age (hazard ratio [HR], 1.03; 95% confidence interval [CI], 1.01‐1.06; P = 0.019), diabetes (HR, 1.78; 95% CI, 1.09‐2.92; P = 0.022), prior history of CVD (HR, 2.46; 95% CI, 1.45‐4.16; P < 0.001), and serum TN > 0.07 ng/mL (HR, 1.98; 95% CI, 1.23‐3.18; P = 0.005) were independently associated with CVD in the long term. Smoking history (ever), sex, hyperlipidemia, and serum ferritin levels were not predictive of CVD. Tacrolimus use versus noncalcineurin‐based immunosuppression (HR, 0.26; 95% CI, 0.14‐0.49; P < 0.001) was associated with reduced risk of CVD but not versus cyclosporine (HR, 0.67; 95% CI, 0.30‐1.49; P = 0.322). CVD is common after LT. Independent of MS, more data are needed to identify nonconventional risk factors and biomarkers like serum TN. Curbing weight gain in the early months after transplant may impact MS and subsequent CVD in the long term. Liver Transpl 21:889‐896, 2015. © 2015 AASLD.